2020
DOI: 10.1111/tct.13148
|View full text |Cite
|
Sign up to set email alerts
|

Simulated on‐call: time well spent

Abstract: Background: Newly qualified doctors feel unprepared to take responsibility for patients and work independently, lacking confidence in skills essential during on-calls. We designed this study to assess the educational value of simulated on-calls and to explore the characteristics of this approach that contribute to improving students' preparedness. Methods: A total of 38 final-year medical students attended two sessions, each including a simulated on-call followed by a one-to-one debriefing. Students' confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Combined with the results of our study, these findings suggest that SBME could provide a valuable addition to the teaching repertoire of CPT teachers, especially since an increasing number of medical schools already have simulation mannequins available. Already in 2014, more than 80% of medical schools in the United States had an incorporated simulation‐based instruction within all 4 years of the undergraduate curriculum 30 . In order to successfully incorporate SBME into the medical curriculum, it is important that students get accustomed to this method from an early stage 31 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined with the results of our study, these findings suggest that SBME could provide a valuable addition to the teaching repertoire of CPT teachers, especially since an increasing number of medical schools already have simulation mannequins available. Already in 2014, more than 80% of medical schools in the United States had an incorporated simulation‐based instruction within all 4 years of the undergraduate curriculum 30 . In order to successfully incorporate SBME into the medical curriculum, it is important that students get accustomed to this method from an early stage 31 .…”
Section: Discussionmentioning
confidence: 99%
“…27 all 4 years of the undergraduate curriculum. 30 In order to successfully incorporate SBME into the medical curriculum, it is important that students get accustomed to this method from an early stage. 31 Students should be able to repetitively practice their skills using a wide variety of patient scenarios and increasing level of difficulty throughout the medical curriculum.…”
Section: What This Study Adds?mentioning
confidence: 99%
“…Additionally, whilst we appreciate that the treatment of cardiac arrests requires a team effort, a recent study by Misquita et al found that individual-based simulation was more beneficial than group-based simulation. 2 The medical students appreciated the added responsibility for their decisions, gave more thought to the possible ramifications of their actions and were able to better understand their limits. Furthermore, the study also revealed that one-to-one feedback was preferred by students as they felt more comfortable asking clarifying questions regarding their performance.…”
Section: Dear Editormentioning
confidence: 99%
“…Furthermore, the study also revealed that one-to-one feedback was preferred by students as they felt more comfortable asking clarifying questions regarding their performance. 2 This could have potentially improved self-reported knowledge and confidence scores and reduced the need for repeating the simulation several times per intern.…”
Section: Dear Editormentioning
confidence: 99%